Safety of anti-rheumatic drugs for rheumatoid arthritis in pregnancy and lactation - Ngian, G.; Briggs, Andrew; Ackerman, I.; Van Doornum, S. (2016)
Women with rheumatoid arthritis (RA) are often of childbearing age and therefore questions regarding reproductive health and the use of medications, including disease-modifying anti-rheumatic drugs (DMARDs) may arise during the clinical consultation. Each patient requires individual assessment in order to effectively manage the disease while minimizing any treatment-associated risks to the fetus. Although good-quality controlled trials are lacking, there is an increasing volume of evidence surrounding the use of immunosuppressive therapies in pregnancy and lactation. This review summarizes the currently available information which can be of benefit to clinicians guiding patients and their families through the risks and benefits of continuing RA therapy during pregnancy and lactation. Further studies and ongoing surveillance of drug safety in pregnancy are required to resolve the uncertainties that remain regarding synthetic and biologic DMARDs.